Centro de Pesquisas e Parque de Integração Urbana dos Igarapés de Manaus - Müller, Camilla Sandoval (Brasil, 2022)
This lecture has as the main goal the creation of the Research Center and Urban Integration Park at Manaus, Amazonas. This project has as the main premise the overall study of Manaus’ watercourses in its physical form, as well as the phenomenon and presence of urban agglomerations in its shores. For this reason, this project has two main parts: the Research Center (composed by laboratories, classrooms and other structures necessary for the development of science), and the Urban Integration Park (which will serve as a urban studies model lab, that will put into practice the studies and urban theories). The land lot chosen for this study is located in Parque Dez de Novembro neighborhood, specifically at the crossroads between avenues Darcy Vargas and Maceió: place where the Parque Dez’ Balneary – an urban leisure spot – used to be until the 1970s, where it was deactivated. This land lot also has a physical connection with Amazonas State University’s Tech School, which will serve as an supportive entity of this project.